2015
DOI: 10.1007/s00267-015-0466-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Rapid Assessment Methods to Determine Streamflow Duration Classes in the Pacific Northwest, USA

Abstract: United States Supreme Court rulings have created uncertainty regarding U.S. Clean Water Act (CWA) authority over certain waters, and established new data and analytical requirements for determining CWA jurisdiction. Thus, rapid assessment methods are needed that can differentiate between ephemeral, intermittent, and perennial streams. We report on the validation of several methods. The first (Interim Method) was developed through best professional judgment (BPJ); an alternative (Revised Method) resulted from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…Tracer experiments using 15 N, bromide, salt solutions, fluorescing particles, or other conservative compounds have also been conducted to assess the frequency, magnitude, and timing of flowpaths in aquatic systems (Mulholland et al 2004;Bencala et al 2011;O'Brien et al 2012). Furthermore, sensors that detect the presence of water in streams can be used to determine the duration of functional connections (McDonough et al 2015) and can assist in characterizing the hydrologic permanence of streams, which can inform estimates of the duration of connections (Leibowitz et al 2008;Fritz et al 2009;Nadeau et al 2015). Structural indices derived from topography, alone or in combination with other watershed characteristics (e.g., infiltration and storage capacity, presence of barriers), can be used to predict structural patterns in the spatial frequency, magnitude, and spatial extent of potential connections.…”
Section: Quantifying Connectivitymentioning
confidence: 99%
“…Tracer experiments using 15 N, bromide, salt solutions, fluorescing particles, or other conservative compounds have also been conducted to assess the frequency, magnitude, and timing of flowpaths in aquatic systems (Mulholland et al 2004;Bencala et al 2011;O'Brien et al 2012). Furthermore, sensors that detect the presence of water in streams can be used to determine the duration of functional connections (McDonough et al 2015) and can assist in characterizing the hydrologic permanence of streams, which can inform estimates of the duration of connections (Leibowitz et al 2008;Fritz et al 2009;Nadeau et al 2015). Structural indices derived from topography, alone or in combination with other watershed characteristics (e.g., infiltration and storage capacity, presence of barriers), can be used to predict structural patterns in the spatial frequency, magnitude, and spatial extent of potential connections.…”
Section: Quantifying Connectivitymentioning
confidence: 99%
“…Improved understanding of temporal and spatial patterns in flow intermittency is fundamentally important for effective river management (Snelder et al, 2013). However, this has been impeded by the scarcity of information about the distribution and hydrologic characteristics of intermittent streams (Acuña et al, 2017;Datry et al, 2011;Nadeau et al, 2015). This has resulted in increased research focus on quantifying the distribution of intermittent streams in particular geographic regions, such as France (Snelder et al, 2013), Australia (Kennard et al, 2010b), Spain and North America (de Vries et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Field surveys in nine regions of the US estimated that most regions have more than 200% intermittent stream channel length than depicted in NHDPlus maps (1: 24,000 or 1: 100,000 scales; Fritz et al, 2013). Nadeau et al (2015) also found poor agreement between field verified intermittent streams and USGS 1:24,000 maps in the Pacific Northwest. We found that the percent of wetlands connected to stream outlets by intermittent streams was 135% higher than our estimate of such wetlands from NHDPlus HR geospatial data.…”
Section: Geospatial Analysis Of Connectivitymentioning
confidence: 97%
“…However, the value of these non-perennial waterways for protection has been undermined by the historical gap in identifying the extent and connectivity of these intermittent and ephemeral streams on maps of common scale (i.e., 1:24,000; Leibowitz et al, 2008;Benstead and Leigh, 2012;Datry et al, 2014;Ryan, 2017;Wohl, 2017). With the advancement of improved mapping, modeling, and field work in recent years, the extent and functional importance of intermittent streams (Benstead and Leigh, 2012;Fritz et al, 2013;Leigh et al, 2015;Nadeau et al, 2015;Williamson et al, 2015) and their connections to wetlands (Tiner, 2003;Marton et al, 2015;Lane and D'Amico, 2016;Rains et al, 2016) can be refined.…”
Section: Introductionmentioning
confidence: 99%